If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 3 = 2(x + -1) Reorder the terms: 3 + Y = 2(x + -1) Reorder the terms: 3 + Y = 2(-1 + x) 3 + Y = (-1 * 2 + x * 2) 3 + Y = (-2 + 2x) Solving 3 + Y = -2 + 2x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + Y = -2 + -3 + 2x Combine like terms: 3 + -3 = 0 0 + Y = -2 + -3 + 2x Y = -2 + -3 + 2x Combine like terms: -2 + -3 = -5 Y = -5 + 2x Simplifying Y = -5 + 2x
| .4x-.3x+.4x=3 | | 5+n=10 | | 4a+7(a+2)= | | 3(z-1)=5z+3+2z | | 2(x+9)+3x-5=8 | | 3-5(z+1)=2+(z-4) | | 3x+134=5x+6 | | 4f-2(f+5)=f+8 | | 9n+21=6n+6 | | X^2+4x=163 | | 20v=19.9v-1.58 | | x-6-6x=1 | | 20v=19.9-1.58 | | -18+14s-20=11s+19 | | (3t/10)=(1/2) | | 9n-21+6n=6 | | -18+14-20=11s+19 | | 10x+y=7 | | -18h=18-16h | | v+.7t=r | | 1+20t=3t-14+18t | | 11x+10=10x+5 | | r=.7t+v | | -8-18j=6j-8 | | y-12=5y-15 | | 15m=16+16m | | z^2-5z+6= | | 5n-7=5(n-2)+3 | | 4(4z+2)-9=111 | | 9x+3=6x+48 | | -14-12v=-20v+18 | | 3(2x-5)-7=4(x-9) |